TOPOGRAPHIC AND ANATOMICAL JUSTIFICATION OF THE APPROACH TO PERFORMING INTRAPERITONEAL INJECTION - Yakymenko, O.G.; Suchok, S.O. (World of Medicine and Biology, 2023)
Performing intraperitoneal injections in rats is one of the most common and accessible methods of administering drugs and anesthetics in an experiment. In 74 % of cases (32/43), the cecum was located on the right and along the midline. A midline was performed in the laboratory animal from the external opening of the urethra to the xiphoid process. Through the point that divides it in half, a perpendicular was drawn along the left half of the abdomen’s front wall. A bisector formed at an angle of 90° to the inguinal fold was lowered into the left inguinal region. The injection site was defined as a point lying on ½ of the line formed by the bisector of the angle. The proposed technical solution has significant advantages: it justifies the place and point of intraperitoneal injection and reduces the risk of iatrogenic damage to abdominal organs.